2021
DOI: 10.3389/fragi.2021.725884
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Molecular Mechanisms of Cardiovascular Aging

Abstract: Cardiovascular disease (CVD) is still the leading cause of illness and death in the Western world. Cardiovascular aging is a progressive modification occurring in cardiac and vascular morphology and physiology where increased endothelial dysfunction and arterial stiffness are observed, generally accompanied by increased systolic blood pressure and augmented pulse pressure. The effects of biological sex on cardiovascular pathophysiology have long been known. The incidence of hypertension is higher in men, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 348 publications
0
11
0
Order By: Relevance
“…52 Amidst the multiple mechanisms implicated in overall vascular aging, several features are noted to be more sex specific. 53 At the outset, the vasculature in females compare to males has been found to exhibit greater mineralocorticoid receptor expression 13 and lesser baroreflex sensitivity, 54,55 which set the stage for what appears to be greater salt sensitivity 56 and differential neural-hormonal-hemodynamic regulation of blood pressure 57 with aging. In addition, in the setting of hormone receptor expression throughout the vasculature, [58][59][60] studies have found that younger and premenopausal arteries exhibit limited amounts of endothelial inflammation as well as a robust vasodilatory capacity that is mediated by nitric oxide and serves to limit oxidative damage.…”
Section: Sex-related Differences In Vascular Aging Mechanismsmentioning
confidence: 99%
“…52 Amidst the multiple mechanisms implicated in overall vascular aging, several features are noted to be more sex specific. 53 At the outset, the vasculature in females compare to males has been found to exhibit greater mineralocorticoid receptor expression 13 and lesser baroreflex sensitivity, 54,55 which set the stage for what appears to be greater salt sensitivity 56 and differential neural-hormonal-hemodynamic regulation of blood pressure 57 with aging. In addition, in the setting of hormone receptor expression throughout the vasculature, [58][59][60] studies have found that younger and premenopausal arteries exhibit limited amounts of endothelial inflammation as well as a robust vasodilatory capacity that is mediated by nitric oxide and serves to limit oxidative damage.…”
Section: Sex-related Differences In Vascular Aging Mechanismsmentioning
confidence: 99%
“…Moreover, analyses carried out on the heart showed that the profiles of functionally relevant proteins and their isoforms differed in animals of both sexes. These differences, included more than twenty-two proteins and increased significantly with the age of the mice ( 20 ). Male-specific expression of Y-linked genes was observed not only in mouse heart, but also in the human myocardium (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, because the summary-level data did not provide information on gender, we could not evaluate the causal association of CD with cardiovascular diseases in males and females, respectively. Epidemiological studies suggested that gender may play a role in cardiovascular disease susceptibility and mortality ( 30 , 31 ). Future large-scale MR studies using individual-level data are required to analyze gender-specific associations.…”
Section: Discussionmentioning
confidence: 99%